1997
DOI: 10.1097/00004836-199709000-00017
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Peyer's Patches in the Age-Related Incidence of Crohn's Disease

Abstract: Recently researchers have suggested that clinical subsets of Crohn's disease occur, which are variously described as inflammatory, fibrostenotic, and fistulizing. In addition, it has been observed that within families with multiple cases, often there is concordance of the site and type of disease. The lesions of Crohn's disease occur in segments that suggest that distribution of Peyer's patches. When the age-related incidence of Crohn's disease was plotted for all countries from which such data were available,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 32 publications
2
43
0
2
Order By: Relevance
“…19 We found that the lymphoid aggregate component of mucosa-associated lymphoid tissue is altered even in the uninvolved colorectal lining of inflammatory bowel diseases. Our finding supports a primary pathogenic involvement of the lymphoid aggregate system in Crohn's disease and in ulcerative colitis, since it suggests the presence of an altered mucosal substrate prone to extension or to relapse of the inflammatory disease.…”
Section: Discussionmentioning
confidence: 74%
“…19 We found that the lymphoid aggregate component of mucosa-associated lymphoid tissue is altered even in the uninvolved colorectal lining of inflammatory bowel diseases. Our finding supports a primary pathogenic involvement of the lymphoid aggregate system in Crohn's disease and in ulcerative colitis, since it suggests the presence of an altered mucosal substrate prone to extension or to relapse of the inflammatory disease.…”
Section: Discussionmentioning
confidence: 74%
“…A correlation exists between peak of CD case frequency (between 15 and 25 years old) and peak representing the number of PPs according to age, suggesting that CD develops as an inflammatory process specifically targeting these important lymphoid structures (36). Moreover, recent studies reported a defect in the intestinal barrier to control bacterial translocation across PPs of CD (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Although morbidity and mortality are relatively low, some types of disease show a peak incidence in the adolescent years. The highest incidence of hepatitis (/) and infections of the gastrointestinal tract (8) have been noted in the adolescent age range. The highest rate of near-fatal asthma attacks occurs in adolescence (9).…”
Section: Major Health Problems Of Adolescencementioning
confidence: 99%